2023
DOI: 10.3390/cancers15235624
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraception and the Risk of Breast Cancer in Women of Reproductive Age: A Meta-Analysis

Luz Angela Torres-de la Roche,
Angélica Acevedo-Mesa,
Ingrid Lizeth Lizarazo
et al.

Abstract: This study aims to summarize evidence from observational studies about the lifetime use of HC and the risk of BC in women of reproductive age. The PubMed, Cochrane, and EMBASE databases were searched for observational studies published from 2015 to February 2022. Meta-analyses were performed using adjusted odds ratios and relative risks with a random-effects model using the I2 statistic to quantify the heterogeneity among studies. Of the 724 studies identified, 650 were screened for title/abstract selection, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…Based on a review of five literatures [17,18,[22][23][24], it was found that the use of hormonal contraceptives has a significant effect and is a risk factor for breast cancer incidence with a considerable risk. This finding is consistent with previous systematic reviews supported by meta-analysis [2,11,25,26].…”
Section: Discussionsupporting
confidence: 93%
“…Based on a review of five literatures [17,18,[22][23][24], it was found that the use of hormonal contraceptives has a significant effect and is a risk factor for breast cancer incidence with a considerable risk. This finding is consistent with previous systematic reviews supported by meta-analysis [2,11,25,26].…”
Section: Discussionsupporting
confidence: 93%